Conflict Management and Dialogue with Diverse Students: Novice Teachers' Approaches and Concerns - Christina A. Parker; Kathy Bickmore (University of Windsor, 2012)
Teaching, in settings with globalized migrant populations, does not automatically lead to peace. For example, social conflict and exclusion may be exacerbated when Othering narratives (in interpersonal interaction or curriculum texts) are not contested. However, paradoxically, in pedagogies that do invite discussion of conflicting viewpoints, marginalized students may be reluctant to voice divergent perspectives, or may be treated disrespectfully. We probed this puzzle through an exploratory quantitative and qualitative survey of how 68 novice teachers approached conflict and ethnocultural diversity in their classrooms. Most expressed some confidence in their capacities to address conflict, though many reported feeling alone, intimidated, or unwilling to engage students in constructive conflict talk. Several emphasized that responding to students' diversities was an important part of their conflict management, while others said they treated all students the same way. Most said they needed more education and support in order to address conflict educatively in their classrooms.